Outbreak of monensin poisoning in equines: clinical signs, histopathologic findings and chromatographic diagnosis - Nelcimara Mirley de Souza Correia; Wagner Luís Fernandes; Mary Ane Gonçalves Lana; Isadora David Tavares de Moraes; Julia Paiva Nunes; Jéssyca Ataíde Ferreira; Monica Chacon de Vicente; Alexandre Có Mangoni Barros; Ana Rita Rodrigues Guimarães; Murilo Rodrigues de Souza; Ana Luísa Soares de Miranda; Marina Pacheco Miguel; et al. (Ciência Rural)
ABSTRACT: Ionophores are polyether antibiotics used in animal production for ruminants and birds to promote growth and exert coccidiostat action. Despite the benefits of their use, poisonings have also been reported in several species. Equines are very sensitive, and most cases involve mistaken intake of feed intended for ruminants. This research described an outbreak of ionophore poisoning in seven horses and a mule that ingested livestock concentrate, confirmed by a chromatographic diagnostic method. A six-year-old horse was presented with clinical signs of sialorrhea, sweating, ataxia, prostration, anorexia, muscle tremors, lateral recumbency, posterior lateral decubitus, which began the day before. Laboratory tests showed increased AST (aspartate aminotransferase) and CK (creatine kinase) activities. Electrocardiogram revealed ventricular tachycardia. Due to the severity of the condition, the patient was euthanized on the day of admission, and a necropsy was performed, in which skeletal and cardiac muscle tissues were collected. Histology revealed multifocal necrosis in cardiomyocytes, necrosis, edema and hemorrhage in skeletal muscle. A visit was made to the property to evaluate other animals and collect samples for laboratory tests. All remaining animals underwent physical examination, two of which showed serious clinical signs. Three animals showed normocytic normochromic anemia, four increased creatinine, two had increased AST activity and all had increased CK activity. Among the poisoned animals, two died on the property. Liver sample from the first euthanized horse was examined by liquid chromatography coupled with mass spectrometry, identifying 51.59 µg/kg of monensin. It is concluded that, despite the recovery of the animals, the toxic action of the ionophore can cause injuries that affect equine health and welfare. The feasibility of chromatographic analysis is essential for a definitive diagnosis and must be subsequently developed together with reference values for tissue residues and maximum tolerated doses.